Influenza Viral Membrane Deformation Due to Refolding of HA-Protein: Two-Dimensional Model and Analysis (Advances in Applied Mathematics and Mechanics, 2010)
In this paper we study influenza viral membrane deformation relatedto the refolding of Hemagglutinin (HA) protein. The focus of thepaper is to understand membrane deformation and budding due toexperimentally observed linear HA-protein clusters, which have notbeen mathematically studied before. The viral membrane is modeled asa two dimensional incompressible lipid bilayer with bendingrigidity. For tensionless membranes, we derive an analyticalsolution while for membrane under tension we solve the problemnumerically. Our solution for tensionless membranes shows that theheight of membrane deformation increases monotonically with thebending moment exerted by HA-proteins and attains its maximum whenthe size of the protein cluster reaches a critical value. Ourresults also show that the hypothesis of dimple formation proposedin the literature is valid in the two dimensional setting. Ourcomparative study of axisymmetric HA-clusters and linear HA-clustersreveals that the linear HA-clusters are not favorable to provide asufficient energy required to overcome an energy barrier for asuccessful fusion, despite their capability to cause membranedeformation and budding.